Development and quality evaluation of danbunama (meat floss) - a Nigerian shredded meat product (2014)
Danbunama (DB) is a shredded meat product that is light, easy to pack and nutrient retaining and is traditionally produced from beef. A completely randomized design was employed to study the effect of three meat types of beef, chevon and pork on quality attributes of DB. Proximate composition of the raw meats and their respective DB was determined using standard procedures. The Eating Quality (EQ) was determined using a 9-point hedonic scale. Thiobarbituric Acid Reactive Substances (TBARS) was employed to assess shelf stability of the product. Raw meat protein ranged from 21.2 to 22.9% while the moisture content varied from 64.14 to 71.98%. The product yields were 70.1, 74.1 and 68.9% for Beef Danbunama (BDB), Chevon Danbunama (CDB) and Pork Danbunama (PDB) respectively. Chevon Danbunama has the highest protein (46.73%) followed by PDB (41.78%) while BDB has the least value (39.75%). The overall acceptability for BDB (7.4) was higher (P<0.05) than for CDB (6.6) and PDB (6.2). Pork Danbunama had the least TBARS compared to BDB and CDB irrespective of the length of storage. Danbunama can be produced using any of the meat types without compromising yield and its nutritional value.